Tyler Perry's Madea's Family reunion - Perry, Tyler (Santa Monica, CA : Lions Gate Entertainment, 2006)
In addition to being saddled with an unruly foster teen, Madea has two troubled nieces to deal with. Lisa is engaged to an abusive and controlling investment banker and Vanessa is finding it difficult to open herself to the affection of a bus driver/artist Frankie because of childhood abuse. Wreaking havoc on both of the girls's lives is their mother Victoria.
Title from disc label.
Based on the play by Tyler Perry.
Originally released as a feature film in 2006.
Special features: optional director commentary; deleted scenes; the making of 'Madea's family reunion'; marriage Madea style; Gaither Plantation; making the music; trailers.
Keywords: Matriarchy -- Drama; Family reunions -- United States -- Drama; Foster parents -- United States -- Drama